PENGARUH PROFITABILITAS, KESEMPATAN INVESTASI, DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN TUNAI - Chayati, Nuning Nur; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine empirically the influence of profitability, investment decision, and leverage to the cash dividend policy. The dependent variable of this research is cash dividend policy, meanwhile the independent variables are profitability, investment decision, and leverage. The population is property, real estate, and building construction companies which are listed in Indonesia Stock Exchange in 2011-2015 periods. The sample collection technique has been done by using purposive sampling. Based on the criteria, 18 property, real estate, and building construction companies have been selected as the research samples. The analysis instrument has been carried out by using multiple linear regressions with the model statutes test i.e. the F test of coefficient determination (R2) and hypothesis test (t-test). The classic assumption test has been carried out in this research i.e.: normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Based on the result of the research, it has been found that there is profitability (ROA) which gives significant and negative influence to the cash dividend policy. The investment opportunity give significant and positive influence to the cash dividend policy. Leverage does not have any significant influence because the significance value is greater than 0.05.Keywords: Cash Dividend policy, profitability, investment opportunity, leverage.